2014
DOI: 10.1002/jbm.a.35346
|View full text |Cite
|
Sign up to set email alerts
|

VA‐086 methacrylate gelatine photopolymerizable hydrogels: A parametric study for highly biocompatible 3D cell embedding

Abstract: The ability to replicate in vitro the native extracellular matrix (ECM) features and to control the three-dimensional (3D) cell organization plays a fundamental role in obtaining functional engineered bioconstructs. In tissue engineering (TE) applications, hydrogels have been successfully implied as biomatrices for 3D cell embedding, exhibiting high similarities to the natural ECM and holding easily tunable mechanical properties. In the present study, we characterized a promising photocrosslinking process to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
73
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(74 citation statements)
references
References 32 publications
1
73
0
Order By: Relevance
“…Photocrosslinking via UV light (250 nm < λ < 400 nm) relies on the use of photoinitiators such as Irgacure 2959 26, 27 . However, alternative photoinitiators such as VA-086, that absorb safer UV ranges (≈405 nm) than Irgacure 2959 and lead to enhanced cytocompatibility have been recently described 33 . UV light photons cause dissociation of the photoinitiator into two radicals, which cause radical formation on the methacryloyl groups.…”
Section: Resultsmentioning
confidence: 99%
“…Photocrosslinking via UV light (250 nm < λ < 400 nm) relies on the use of photoinitiators such as Irgacure 2959 26, 27 . However, alternative photoinitiators such as VA-086, that absorb safer UV ranges (≈405 nm) than Irgacure 2959 and lead to enhanced cytocompatibility have been recently described 33 . UV light photons cause dissociation of the photoinitiator into two radicals, which cause radical formation on the methacryloyl groups.…”
Section: Resultsmentioning
confidence: 99%
“…However, there are concerns related to the cytotoxicity of the free radicals generated using I2959 for fast dividing cell lines . Therefore, in search for a more viable photoinitiator, previous studies using alginate and gelatin‐based hydrogels have demonstrated that a water‐soluble Azo initiator 2,2′‐azobis[2‐methyl‐ N ‐(2‐hydroxyethyl)propionamide] (VA086) is more cytocompatible and hence can serve as a promising alternative to I2959 for photochemical crosslinking of natural hydrogels …”
Section: Introductionmentioning
confidence: 99%
“…12,13 Therefore, in search for a more viable photoinitiator, previous studies using alginate and gelatin-based hydrogels have demonstrated that a water-soluble Azo initiator 2,2 0 -azobis [2-methyl-N-(2-hydroxyethyl)propionamide] (VA086) is more cytocompatible and hence can serve as a promising alternative to I2959 for photochemical crosslinking of natural hydrogels. [14][15][16][17][18][19] Collagen scaffolds are commonly used for tissue engineering applications [20][21][22] because of their resemblance to the biological properties of most native tissues. While gelatin and collagen have identical amino acid sequences, the secondary structure of these proteins is different and gelatin scaffolds are weaker than collagen scaffolds.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we exploited chemically modified gelatin (gel‐MOD) with methacrylate groups that can be cross‐linked with UV irradiation in the presence of a photoinitiator (Van Den Bulcke et al, ), as an encapsulation material for valvular microtissues. Two different w / v % gel‐MOD hydrogels were generated and cross‐linked in the presence of the photoinitiator Irgacure 2959 (Irg), which is considered as the golden standard for gel‐MOD cross‐linking, or VA‐086 (VA), which has been shown to be a more cytocompatible photoinitiator (Billiet et al, ; Occhetta et al, ; Rouillard et al, ). Physical and biomechanical analysis was performed to analyze hydrogel properties (gel fraction, swelling ratio, and stiffness).…”
Section: Introductionmentioning
confidence: 99%